Growth Response of Toona sureni to Providing Goat Manure Compost on Planting Media ex Gold Mine - Reci Sartika; M. Mardhiansyah; Pebriandi Pebriandi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Mining activities affect the balance of the soil surface ecosystem, decreasing soil productivity which causes the chemical, biological, and physical properties of the soil to be disturbed, as well as environmental quality. The purpose of this study was to determine the effect and the best composition of a mixture of compost and former gold mine soil in the growth of suren seedlings. This study consisted of 4 (four) treatments and 5 (five) replications resulting in 20 experimental units. The treatment of compost fertilizer in this study can be seen as follows: D1 = no compost/control, D2 = 25% compost + 75% ex-gold mine soil, D3 = 50% compost + 50% ex-gold mine soil, D4 = 75% compost + 25% ex-gold mine soil. The observation parameters are the percentage of life, height increase, plant dry weight and seedling quality index (IMB). The results showed that the application of goat manure compost had a significant effect on the growth of suren seedlings. Treatment composition D4 (75% compost fertilizer + 25% gold mine waste soil) showed the best growth with 100% survival rate, 21, 27 cm height increase, 10.57 g plant dry weight and 0.99 IMB